1994
DOI: 10.1029/93ja01947
|View full text |Cite
|
Sign up to set email alerts
|

Quiet‐time intensifications along the poleward auroral boundary near midnight

Abstract: Radar and optical measurements from Sondrestrom are combined with satellite and Goose Bay data in a study of the poleward edge of the nightside auroral oval during a quiet period. The By and Bz components of the interplanetary magnetic field were close to zero, and the Bx component was ∼8 nT for more than 24 hours. On a large scale, the convection and precipitation patterns remained almost constant during this period; on a small scale, however, the conditions were quite dynamic. At 10‐ to 20‐min intervals the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
103
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 142 publications
(119 citation statements)
references
References 30 publications
16
103
0
Order By: Relevance
“…Thus, the observations are not consistent with the predictions of the Kelvin-Helmholtz instability. b) De la Beaujardière et al (1994) have observed, in the midnight sector and during very quiet conditions, southward flow bursts drifting westward, associated with southward moving auroral arcs. These observations are very similar to the ones presented here in the night sector (see Fig.…”
Section: Origin Of the Flow Burstsmentioning
confidence: 94%
See 2 more Smart Citations
“…Thus, the observations are not consistent with the predictions of the Kelvin-Helmholtz instability. b) De la Beaujardière et al (1994) have observed, in the midnight sector and during very quiet conditions, southward flow bursts drifting westward, associated with southward moving auroral arcs. These observations are very similar to the ones presented here in the night sector (see Fig.…”
Section: Origin Of the Flow Burstsmentioning
confidence: 94%
“…7). De la Beaujardière et al (1994) have associated these events with plasma injections from the tail resulting from enhanced reconnection, essentially on the basis of their analogy with daytime flux transfer events and their association with velocity dispersed ion structures (VDIS). On the other hand, nightside, northsouth elongated auroral structures moving southward have long been observed (Sergeev et al, 1990).…”
Section: Origin Of the Flow Burstsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately no low-altitude satellite measurements of the electrodynamic parameters of such streamers have been reported. Equatorward propagation speeds deduced from auroral imaging range from 270 m/s [de la Beaujardière et al, 1994] and 2 km/s [Nishimura et al, 2010]. A more complete set of low-altitude data would be highly desirable in order to check their consistency with the currents predicted by the braking of BBFs.…”
Section: Auroral Streamersmentioning
confidence: 99%
“…Flows in the nightside ionosphere, however, are more directly controlled by magnetospheric dynamics than by the instantaneous nature of the IMF (e.g. de la Beaujardière et al, 1994;Yeoman and Lühr, 1997;Opgenoorth and Pellinen, 1998;Grocott et al, 2002Grocott et al, , 2003Grocott et al, , 2004. Although the dynamics of the magnetosphere itself are largely influenced by the IMF (e.g.…”
Section: Introductionmentioning
confidence: 99%